Pollen morphology and analysis of Iranian wild pistachio - Behboodi B.S.; Ghaffari M. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
There are three species of wild pistachio: P. atlantica, P. khinjuk and P. vera in the forests of Iran. Rechinger described in Flora Iranica three sub-species of P. atlantica: mutica, kurdica, and cabulica. In order to solve the taxonomical problems between these three sub-species we have compared the morphology of their pollen. Light and scanning electron microscopes were used with conventional methods. All subspecies are perforate and foveolate on the surface. The average diameter of pollen grains was analysed using the SPSS software. According to the analysis based on polar length, the pollen from sub-species cabulica is different from that of other sub-species.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)